Trademark portfolio and enterprise performance: Systematic literature review - Huaqing, r.; Pereira, L.; Xiao, y. (International Journal of Intellectual Property Management, 2022)
Since 2002, the number of trademark registration applications in China has continued to blowout, ranked first in the world. However, the discussion on the motivation of trademark registration and the value of registered trademarks has also become a topic of common concern in the theoretical and practical circles. This paper constructs the trademark portfolio matrix from two dimensions of trademark symbol attribute and registration category, and analyses the impact of different trademark portfolios on firm performance theoretically. This will further analyse the rationality of enterprise registered trademark behaviour and the reasons behind the surge of registered trademark applications in China, so as to provide a reference path for the research of trademark value.